2019
DOI: 10.1002/uog.19041
|View full text |Cite
|
Sign up to set email alerts
|

Home blood‐pressure monitoring in a hypertensive pregnant population: cost‐minimization study

Abstract: HBPM in hypertensive pregnancies appears to be cost-saving compared with traditional monitoring, without compromising maternal, fetal or neonatal safety. Larger studies are required to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 22 publications
(28 reference statements)
2
52
0
1
Order By: Relevance
“…These women are likely to benefit from closer blood pressure monitoring that can be performed by using different approaches and tools. For instance, the introduction of telemonitoring system in pregnancies has made the blood pressure monitoring more accessible and cost-saving [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…These women are likely to benefit from closer blood pressure monitoring that can be performed by using different approaches and tools. For instance, the introduction of telemonitoring system in pregnancies has made the blood pressure monitoring more accessible and cost-saving [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our recent work has demonstrated that HBPM reduces the number of hospital visits without compromising maternal and fetal outcomes. Furthermore, HBPM was found to be cost‐effective, with an average saving per week of £286.53 in the group of women following HBPM using a dedicated app, compared with those undergoing traditional monitoring at the hospital/clinic. Despite these potential benefits, only a limited number of studies have compared blood‐pressure values recorded at home with those recorded at the clinic, with conflicting results reported.…”
Section: Introductionmentioning
confidence: 99%
“…Second, UK government agencies have procured and validated BP monitors for purchase by hospitals, for domiciliary use by hypertensive pregnant women. Third, use of BP apps is being encouraged to facilitate recording of BP and transmission of BP values to care providers; K2 Hampton (https://www.k2ms.com) is the only pregnancy BP app certified as a Class-I medical device in the UK and extensively evaluated within the NHS [5][6][7] .…”
Section: Measure Bp With Device Validated For Use In Pregnancymentioning
confidence: 99%
“…The implications on pregnancy outcomes and costs of a reliance on HBPM to replace many clinic measurements are unknown. Preliminary evidence in hypertensive women attending for specialist care suggests that use of HBPM and a BP app may reduce outpatient healthcare utilization (even among women with recently diagnosed gestational hypertension 5 ) and costs 7 .…”
Section: Measure Bp With Device Validated For Use In Pregnancymentioning
confidence: 99%